Volume 10: Ocean Renewable Energy 2019
DOI: 10.1115/omae2019-95973
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Optimization of U-Oscillating Water Columns in Random Waves

Abstract: This paper deals with the problem of designing an optimal U - Oscillating Water Column (U-OWC) device equipped with a Wells turbine. Specifically, the paper proposes the implementation of a genetic algorithm for designing a U-OWC exposed to the typical sea states available in the Mediterranean Sea. The first challenge encountered in this problem is the efficient calculation of the U-OWC hydrodynamic parameters. The second challenge relates to the fact that the U-OWC dynamics is governed by two coupled nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[10], where it was shown that the U-OWC configuration exhibited enhanced hydrodynamic performance compared to the traditional OWC, or to the L-shaped OWC. Moreover, the performance of the U-OWC is strongly dependent on its geometrical characteristics [11,12], such as the length and the width of the U-duct, the position of its opening below the mean water level, and the width and height of the inner chamber. Further, the optimal selection and control of the Power Take-Off (PTO) system is critical for maximizing the amount of converted energy [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10], where it was shown that the U-OWC configuration exhibited enhanced hydrodynamic performance compared to the traditional OWC, or to the L-shaped OWC. Moreover, the performance of the U-OWC is strongly dependent on its geometrical characteristics [11,12], such as the length and the width of the U-duct, the position of its opening below the mean water level, and the width and height of the inner chamber. Further, the optimal selection and control of the Power Take-Off (PTO) system is critical for maximizing the amount of converted energy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, statistical linearization has been employed for stochastic response determination and optimization of diverse wave energy harvesting devices [26], including point-absorbers [27], OWCs [28], and arrays of OWCs and U-OWCs [29]. Also, the methodology has found practical applications pertaining, indicatively, to the case study of the U-OWC in the Civitavecchia harbor (Rome, Italy) [30], and to the design of a U-OWC wave power plant to be installed in the Mediterranean Sea [11]. Although statistical linearization has exhibited a high degree of reliability in determining both OWC and U-OWC statistics, note that the horizontal opening of the U-duct is closer to the free surface compared to the traditional OWCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the advantages of the technique, a limited number of papers has applied the SL for WECs [21][22][23][24][25][26][27]. This technique is a valuable tool for estimating the nonlinear response of the system, especially for optimizing a system with a large number of parameters [28] and several sea states [29].…”
Section: Statistical Linearization (Sl)mentioning
confidence: 99%
“…In addition, the mean power is calculated to compare the difference between the traditional FD results with those using SL. In this regard, the linearized form of Equations (5.21) and (5.22) are derived: The response matrix is computed as: 28) where S F (ω) denotes the power spectrum of the excitation, and ( ) T is the transpose conjugate of a matrix. As the wave excites the water column, the power spectrum of the excitation force contain only the first term:…”
Section: Linear System -Frequency Domainmentioning
confidence: 99%